Parental and peer support and modelling in relation to domain-specific physical activity participation in boys and girls from Germany. - Anne K Reimers; Steffen C E Schmidt; Yolanda Demetriou; Isabel Marzi; Alexander Woll (PLoS ONE, 2019)
Background Physical activity (PA) as a precondition of child development is related with social environmental correlates. However, domain-specific PA and gender issues have been neglected in studies on social support and modelling and PA in school-aged children. The aim of this study was to assess the relationships of parental and peer modelling and social support with domain-specific PA participation in a large sample of school-aged children, taking gender into account. Methods 3,505 school children aged 6 to 17 years old participated in the German nationwide 'MoMo' cohort-study. By using the MoMo-PAQ the participants and their parents provided self-report data on perceived social support and social modelling and domain-specific PA participation. Relationships of social environmental variables and the physical outcomes were analysed by logistic regression analyses. Results At secondary school level, girls were less likely than boys to participate in physical activity in and outside of sports clubs, extra-curricular physical activity and in outdoor play (p < 0.05), but at primary school level this pattern only applied to club sport (p < 0.01). Girls also received less social support than boys (p < 0.01). Physical activity participation in all domains was associated with any of the social support and modelling variables and differences between physical activity domains and between boys and girls occurred. Most consistently physical activity in sports clubs was related with the social environmental correlates in boys (primary school: R2 = 0.60; secondary school: R2 = 0.45) and girls (primary school: R2 = 0.53; secondary school: R2 = 0.47). Conclusions In future, reciprocal relationships of social environmental variables and PA should be considered in longitudinal studies to obtain insights into the direction of the associations. Furthermore, interventions encompassing the social environment and focussed particularly on the promotion of domain-specific PA in girls in secondary school-age are warranted.